The Implementation of Akhlaq-Based Curriculum in Islamic Schools - Robitoh Firoza Wahyu Nafia; Sania Barlinty Azhar; Mokhamad Yossi Kemara Oktadi (JISEI: Journal of Islamic Studies and Educational Innovation, 2025)
Moral-based education is an important element in the Islamic education system that aims to shape the character of students in accordance with Islamic values. This study aims to analyze the implementation of moral-based curriculum in Islamic schools, including the approach, strategies, and challenges faced in its implementation. The research method used is qualitative with a case study approach in several Islamic schools. The results of the study indicate that the implementation of moral-based curriculum involves the integration of moral values ​​in subjects, extracurricular activities, and school culture. However, several challenges such as lack of resources and systematic evaluation are still major obstacles. This study recommends strengthening teacher training and more concrete policy support to ensure the sustainability of the moral-based curriculum.